Tunable Perfect Absorption Structures Based on Cavity Coupling and Plasmon Hybrid Mode - Yuanhang Zhao; Zizheng Li; Qiang Li; Kun Wang; Jinbo Gao; Ke Wang; Haigui Yang; Xiaoyi Wang; Tongtong Wang; Yanchao Wang; Jinsong Gao (IEEE Photonics Journal, 2021)
We report a theoretical study of a perfect absorber based on the metal-insulator-metal (MIM) structure, which achieves perfect absorption of single and double peaks in the visible range. The top Ag and middle SiO2 are arranged in a periodic nanopillar array. Adjusting the structural parameters of the nanopillars to indirectly control the absorption spectrum, theoretically the maximum single-peak absorption can reach more than 99.0% and the maximum double-peak absorption can reach more than 90.0%. We investigate its absorption mechanism through simulations and calculations, and explain the results well with the SPP scattering mode and F-P cavity theory. We find that through the double-peak absorption process, the mode split phenomenon appears as the thickness of SiO2 increases. Therefore, the selective appearance of absorption peaks can be achieved, which provides the possibility of application in absorbers.